Numerical and experimental analysis of a horizontal ground-coupled heat pump system - Esen, Hikmet; Inalli, Mustafa; Esen, Mehmet (Pergamon-Elsevier Science Ltd, 2007)
The main objective of this work is to evaluate a heat pump system using the ground as a source of heat. A ground-coupled heat pump (GCHP) system has been installed and tested at the test room, University of Firat, Elazig, Turkey. Results obtained during experimental testing are presented and discussed here. The coefficient of performance (COPsys) of the GCHP system is determined from the measured data. A numerical model of heat transfer in the ground was developed for determining the temperature distribution in the vicinity of the pipe. The finite difference approximation is used for numerical analysis. It is observed that the numerical results agree with the experimental results. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: ground coupled heat pump; space heating; performance analysis; temperature distribution